The Effect Of Health Education Using The Snow Balling Method Against Breastfeeding Self Efficacy In Primigravida - Ummah, Faizatul; Sari, Ratih Indah Kartika; Turlina, Lilin; Sholehah, Nasehatus (Jurnal Midpro, 2020)
Self-efficacy of breastfeeding (BSE) is a mother's confidence in her ability to succeed in providing exclusive breastfeeding. To achieve successful care, it takes a strong place to be able to provide exclusive breastfeeding. One effort that can improve the Self-Efficiency of Breastfeeding (BSE) is verbal persuasion that is the support or advice given by others which is enhanced and becomes a source of strength for mothers issued by education by health workers.The study aims to determine the effect of health education with the Snow Balling method on Breastfeeding Self Efficacy in Primigravida mothers.The research design uses the Posstest Only Control Design approach. Samples were taken from 32 Primigravida mothers who were divided into 2 groups randomly. Retrieval of data using the BSES questionnaire and analyzed using the Mann Whitney U Test (Î± <0,05).The results showed that more than Primigravida mothers who were not given health education had a low BSE (average BSES score 12.5), and almost all Primigravida mothers who were given health education about lactation by the snow balling method had high BSE (average average BSES score 20.5). Statistical test results showed that there was an effect of health education with the Snow Balling method on Breastfeeding Self Efficacy in Primigravida mothers (p = 0.004).t is recommended that health workers in providing health education not only use the lecture method but with other more interactive methods such as snow balling.